Chronic Distal Sensory Polyneuropathy Is a Major Contributor to Balance Disturbances in Persons Living With HIV. (15th April 2019) - Sakabumi, Duaa Z.; Moore, Raeanne C.; Tang, Bin; Delaney, Patrick A.; Keltner, John R.; Ellis, Ronald J.
Abstract : Background: Medical comorbidities accumulate in older persons living with HIV (PLWH), causing disability and reduced quality of life. Sensory neuropathy and polypharmacy may contribute to balance difficulties and falls. The contribution of neuropathy is understudied. Objective: To evaluate the contribution of chronic distal sensory polyneuropathy (cDSPN) to balance disturbances among PLWH. Methods: Ambulatory PLWH and HIV− adults (N = 3379) were prospectively studied. All participants underwent a neurologic examination to document objective abnormality diagnostic of cDSPN and reported neuropathy symptoms including pain, paresthesias, and numbness. Participants provided detailed information regarding balance disturbance and falls over the previous 10 years. Balance disturbances were coded as minimal or none and mild-to-moderate. Covariates included age, HIV disease, and treatment characteristics and medications (sedatives, opioids, and antihypertensives). Results: Eleven percent of participants reported balance disturbances at some time during the last 10 years; the rate in PLWH participants exceeding that for HIV− [odds ratio 2.59, 95% confidence interval: 1.85 to 3.64]. Fifty-two percent met criteria for cDSPN. Balance problems were more common in those with cDSPN [odds ratio = 3.3 (2.6–4.3)]. Adjusting for relevant covariates, balance disturbances attributable to cDSPN were more frequent among HIV+ than HIV− (interaction P = 0.001). Among individuals with cDSPN, older participants were much more likely to report balance disturbances than younger ones. Conclusions: cDSPN contributes to balance problems in PLWH. Assessments of cDSPN in older PLWH should be a clinical priority to identify those at risk and to aid in fall prevention and the ensuing consequences, including bone fractures, subdural hematoma, hospital admissions, and fatal injury.